A Dynamic-State Feedback Approach Employing a New State-Space Description for the Fast Wavelet Transform with Multiple Decomposition Levels - Uzinski, J. C. [UNESP]; Paiva, H. M.; Galvão, R. K.H.; Assunção, E. [UNESP]; Duarte, M. A.Q.; Villarreal, F. [UNESP] (Springer Nature, 2017)
This research paper proposes a wavelet-based dynamic-state feedback control strategy in the discrete time domain. In this proposal, the state feedback employs a state-space description for the fast wavelet transform, which is also developed in this article. The feedback gains are obtained through a linear quadratic regulator formulation, with cost weights adjusted according to suitable performance metrics. This proposal brings forward efficient results, as well as more robust systems to external perturbations and sensor noises.
Keywords: Discrete linear quadratic regulator; State feedback control; Wavelet-based dynamic-state feedback